Late Roman pottery discovered at Tibiscum-Iaz, Dacia (middle of the 3rd–4th century AD) - Grumeza, Lavinia (Rei Cretariae Romanae Fautorum Acta, 2017)
The ancient town of Tibiscum was located on the western border of the province of Dacia. The settlement started in AD 106 as a military vicus but at the beginning of the 3rd century AD it became a municipium. Due to its geographical location Tibiscum held the most important role in the defensive system of south-west Dacia, and implicitly, of its capital Ulpia Traiana Sarmizegetusa.